2013
DOI: 10.1073/pnas.1300378110
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependent N-cadherin up-regulation mediates reactive astrogliosis and neuroprotection after brain injury

Abstract: Brain injury induces phenotypic changes in astrocytes, known as reactive astrogliosis, which may influence neuronal survival. Here we show that brain injury induces inositol 1,4,5-trisphosphate (IP 3 )-dependent Ca 2+ signaling in astrocytes, and that the Ca 2+ signaling is required for astrogliosis. We found that type 2 IP 3 receptor knockout (IP 3 R2KO) mice deficient in astrocytic Ca 2+ signaling have impaired reactive astrogliosis and increased injuryassociated neuronal death. We identified N-cadherin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
108
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 36 publications
(42 reference statements)
8
108
0
Order By: Relevance
“…Increased serum levels of N-cadherin can be an indicator of neuronal and /or synaptic loss [38,39]. Similar to most of the other biomarkers, serum N-cadherin levels also showed a biphasic pattern with peaks by day 1 and 14.…”
Section: Neuronal and Glial Injurymentioning
confidence: 76%
“…Increased serum levels of N-cadherin can be an indicator of neuronal and /or synaptic loss [38,39]. Similar to most of the other biomarkers, serum N-cadherin levels also showed a biphasic pattern with peaks by day 1 and 14.…”
Section: Neuronal and Glial Injurymentioning
confidence: 76%
“…Among the cadherin family, N-cadherin has been classified as "nerve-derived", and is known as a key CAM in the brain. N-cadherin has also been reported to be upregulated via cellular-stress signaling after brain injury by using the N-cadherin knockout model [20]. We speculated that GFAP aggregates in AxD astrocytes can evoke cellular stress and upregulated N-cadherin as a stress response.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to this, the same authors have shown that astrocytic calcium signalling and the downstream function of N-cadherin, a calcium-dependent cell -cell adhesion glycoprotein, play indispensable roles in the reactive response to a neocortical stab wound injury (SWI) and, highly relevant to this review, they have linked these mechanisms to ATP signalling [124]. Specifically, they first demonstrated that brain injury induces inositol 1,4,5-trisphosphate (IP3)-dependent Ca 2þ signalling in astrocytes and that this is required for SWI-associated astrogliosis.…”
Section: Parenchymal Astrocytesmentioning
confidence: 94%
“…However, it has to be said that, since then, detection of calcium signalling has undergone significant technical improvements and that lack of sufficiently sensitive methods at those times has prevented the measurement of small, but biologically significant, early astrocytic calcium increases contributing to induction of reactive astrogliosis. In this respect, using transgenic mice that express an ultrasensitive genetically encoded Ca 2þ indicator, YC-Nano50, in an astrocyte-specific manner, Kanemaru and co-workers [124] have recently reported the in vivo visualization of spontaneous subtle and localized astrocytic Ca 2þ signals (Ca 2þ twinkles), which are preferentially displayed in fine astrocytic processes in living mice brain.…”
Section: Parenchymal Astrocytesmentioning
confidence: 99%
See 1 more Smart Citation